Thermal performance investigation of modified flat plate solar collector with dual-function. (5th September 2016) - Zhang, Dong; Li, Jinping; Gao, Zhangwei; Wang, Linjun; Nan, Junhu
Highlights: A solar collector with dual-function is modified from conventional liquid one. The maximum temperature rise of working fluids can reach 60.4 °C. The collector efficiency of air-water compound heating mode can reach 73.4%. The recommended flow rate of air and water are 0.02–0.025 kg/s and 0.06–0.08 kg/s. Abstract: A flat plate solar collector with dual-function was proposed, which was modified from the conventional liquid solar collector. Three working modes were presented, named (A) air heating, (B) water heating and (C) air-water compound heating. Mathematical models for air and water heating modes were developed to investigate the effect of mass flow rate on the thermal performance. An experimental set-up was established in order to test the actual performance of collector. The experimental results show that the average collector efficiency in mode A and B can achieve 51.3% and 51.4% while the mass flow rate of fluid is 0.024 kg/s and 0.13 kg/s, respectively. The maximum temperature rise of air and water reach 60.4 °C and 59.8 °C in the respective two modes. The average of total collector efficiency based on the mode C can reach 73.4%, higher than that of mode A or B. The mass flow rate is a major factor to affect the efficiency, outlet temperature of fluid and heat transfer effectiveness. When the water flow rate exceeds 0.10 kg/s, the heat removal factor increases insignificantly. To balance the efficiency and outlet temperature of fluid, the air flow rate between 0.02 kg/s and 0.025 kg/s is recommended in mode A and the water flow rate between 0.06 kg/s and 0.08 kg/s is recommended in mode B.